PENGARUH PROFITABILITAS, LEVERAGE, GROWTH, SIZE TERHADAP HARGA SAHAM DENGAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lomboan, Ardi Manuel; Sondakh, Jullie J.; Pontoh, Winston (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2016)
The more rapidly business development currently rises tight competition among corporate companies, either national or international. Company does not longer become entity that only focuses to itself thus separate from sosial environment, but become the part of the environment so there is an interaction that arises, caused by the positive response from surrounded environment to its existence. This research purpose is to find out the influence of Profitability, leverage, growth, and size to stock price with company social responsibility disclosure as intervening variable at listed companies in BEI at periode of 2010 - 2012. Its population is companies that are listed in BEI at 2010 – 2012 periode, as much as 525 companies. By using judgement sampling method, it is obtained 55 companies as sample. The used analysis method is path analysis, while research data processing uses computer program IBM SPSS Statistic 22. From testing calculation, it is found that the testing of profitability, leverage, growth, size and company social responsibility disclosure simultaneously have significant influence to stock price of listed companies in BEI. Partially, Profitability does not significantly influence company social responsibility disclosure; Leverage significantly influences to company social responsibility disclosure; Growth does not significantly influence company social responsibility disclosure; Size significantly influence company social responsibility disclosure; Profitabiliy significantly influence stock price; Leverage significantly influence stock price; Growth does not significantly influence stock price; Size significantly influences stock price; company social responsibility disclosure does not significantly influence stock price. Profitability does not significantly influence stock price through company social responsibility disclosure; Leverage significantly influences stock price through company social responsibility disclosure; Growth significantly influence stock price through company social responsibility disclosure; Size does not significantly influence stock price through company social responsibility disclosure Keywords: Profitability, Leverage, Growth, Size, Company Social Responsibility Disclosure, and Stock Price.